Customers satisfaction towards the fast food restaurants' service quality: a case study in McDonald's, Kuching, Sarawak - Lim, Sze Sze (Universiti Malaysia Sarawak (UNIMAS), 2006)
Generally, this study aims to perform the assessment of the customers satisfaction towards the service quality provided by the fast food restaurants- McDonald’s in Kuching area. In this study, five dimensions in SERVQUAL were applied as the indicators of the customers satisfaction. In brief, this study was conducted using survey method in which questionnaires were used as the instrument to collect the data. There were 200 sets of questionnaires had been distributed to the respondents and the response rate is 90 percent. Data collected in this study were analyzed using the descriptive statistic and the inferential statistic which consist of Pearson correlation and single linear regression. The findings of this study showed that majority of the respondents were having the moderate or even high level of satisfaction level towards the services offered by the McDonald’s restaurants in Kuching. Meanwhile, there was a significant relationship between the five SERVQUAL dimensions studied and customers satisfaction. In addition, the findings also found out that service responsiveness is the most dominant dimension in enhancing the customer satisfaction.